Enzymatic reduction of graphene oxide by a secreted hydrogenase - Wang, Yan-Zhai; Liu, Heng-Chi; Wang, Jing-Xian; Nawab, Said; Abbas, Syed Zaghum; Zhu, Daochen; Mi, Jian-Li; Zou, Long; Yong, Yang-Chun (Biochemical engineering journal, 2024)
Although reducing graphene oxide (GO) is a promising method for producing graphene, it involves high energy consumption and serious pollution. Here, an eco-friendly and cost-effective method to reduce GO was developed, in which GO was reduced by a fermentation-medium system containing self-secreted [FeFe]-hydrogenase (CFM-H2ase). It was found that GO could be rapidly reduced by hydrogen which was catalyzed by the fermentation medium of Escherichia coli that heterologously expressed [FeFe] hydrogenase. The reduced GO nanosheets were characterized and confirmed by Raman, XRD, and XPS analysis, which indicated a high reduction ratio was achieved. Further analysis revealed that the [FeFe] hydrogenase secreted by the genetically engineered E. coli cells was responsible for the catalysis of hydrogen-induced GO reduction, which was the underlying mechanism for GO reduction by the CFM-H2ase system. This work demonstrated a new enzymatic approach for GO reduction, which would be helpful in developing a more sustainable graphene industry. [Display omitted] •A new approach for green preparation of graphene was developed.•Fermentation medium with hydrogenase was applied for graphene oxide reduction.•Self-secreted hydrogenase played key role on graphene oxide bioreduction.•This cell-free approach was superior to cell-based preparation of graphene.